ANALYSIS OF THE ROLE OF TOURISM MANAGERS IN CREATING SUSTAINABLE TOURISM IN THE MONKEY FOREST AREA, UBUD, BALI - Insiyah, Lutfiyatul; Meinanda, Erina; Wardani, Heny Ayu; Utami, Shellafie Werdhiningtyas; Andreansyah, Nauval Kaka; Sitohang, Lidya Lestari (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2024)
AbstractThe Monkey Forest area in Ubud, Bali, is popular throughout the world because of its biodiversity and culture. Tourism managers play a key role in realizing sustainable tourism. This study aims to understand the role of tourism managers in achieving sustainable tourism. This study uses a qualitative approach with data collection techniques of observation, interviews, literature study and documentation. The research took place in the period of July – December 2023. The data was collected in the mid of November 2023 under a three days fieldwork in Ubud area. Purposive sampling was used to select the key informants. Data were processed using the Miles and Huberman analysis model, with data reduction and identification of main themes to understand the role of tourism managers in achieving sustainable tourism in the Monkey Forest area. Three themes appear in the analysis include the tourism managers as the service provider, the challenges they face, and their efforts to overcome these challenges. The results suggest that the managers actively support the sustainable tourism practices. However, to obtain a comprehensive overview of sustainable development actors, further research on other tourism stakeholders is needed. AbstrakKawasan Monkey Forest di Ubud, Bali, populer di seluruh dunia karena keberagaman hayati dan budayanya. Pengelola wisata memainkan peran kunci dalam mewujudkan wisata yang berkelanjutan. Studi ini bertujuan untuk memahami peran, tantangan, dan upaya pengelola wisata di Kawasan Monkey Forest dalam mencapai wisata berkelanjutan. Studi ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data observasi, wawancara, studi kepustakaan, dan dokumentasi di Monkey Forest. Penelitian ini berlangsung pada Juli – Desember 2023 dan pengumpulan data dilakukan dalam agenda tiga hari fieldwork di pertengahan November 2023. Purposive sampling digunakan untuk memilih narasumber. Data diolah menggunakan model analisis Miles and Huberman, dengan reduksi data dan identifikasi tema utama untuk memahami peran pengelola wisata dalam mencapai wisata berkelanjutan di kawasan Monkey Forest. Tiga tema yang muncul dalam analisis tersebut antara lain pengelola pariwisata sebagai penyedia jasa, tantangan yang dihadapi, dan upaya mengatasi tantangan tersebut. Hasil penelitian menunjukkan bahwa pengelola berperan aktif dalam mendukung pembangunan wisata berkelanjtutan. Namun demikian, untuk memperoleh gambaran menyeluruh mengenai pelaku pembangunan berkelanjutan, diperlukan penelitian lebih lanjut terhadap peran stakeholder pariwisata lainnya.Kata Kunci: Pengelola Pariwisata; Pariwisata Berkelanjutan; Monkey Forest